Pengakuan dan Pengukuran Aset Dana Bergulir pada BUM Desa Bersama: Antara Regulasi dan Praktik - Tri Nurhayati; Eliada Herwiyanti; Laeli Budiarti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
The transformation of revolving funds from the former PNPM Mandiri program into BUM Desa Bersama entities requires accountable financial management aligned with applicable accounting standards. However, inconsistencies between regulations and accounting practices remain. This study analyzes the recognition and measurement of revolving fund assets at BUM Desa Bersama Ajimas Lestari LKD in Ajibarang and assesses their compliance with Ministerial Regulation of Village PDTT No. 136 of 2022 and SAK ETAP. Using a qualitative case study approach, data are collected through interviews, observation, and documentation involving five internal informants. The results show that asset recognition follows regulations, where revolving funds are recorded as receivables upon loan distribution to Women’s Savings and Loan (SPP) groups at nominal value. However, discrepancies persist in asset measurement and presentation, particularly in receivable classification and the placement of allowance for doubtful accounts under equity. These issues stem from limited human resource capacity, lack of a standardized accounting information system, and weak supervision. Strengthening accounting competence and implementing standardized financial reporting systems are essential to improve accountability and transparency in managing community revolving funds.